2004
DOI: 10.1080/02841850310002970
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution computed tomography in healthy smokers and never‐smokers: a 6‐year follow‐up study of men born in 1933

Abstract: In healthy, elderly never-smokers a low extent of various HRCT findings has to be considered normal. Emphysema, parenchymal nodules, and ground-glass opacities are indicative of smoking-induced disease. Further progress may cease if smoking is stopped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
1
31
1
Order By: Relevance
“…(22)(23)(24)(25)(26) In addition, the EI has been shown to increase with age. (24,26) One group of authors (22) investigated this issue in a cohort of healthy individuals younger than 40 years of age, showing that EI values ≤ 0.35% should be considered normal for volumetric measurements performed with 10-mm collimation, 50 mAs, and a standard reconstruction algorithm; those authors found that the EI was not significantly influenced by age in that age group, a finding that is consistent with those of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…(22)(23)(24)(25)(26) In addition, the EI has been shown to increase with age. (24,26) One group of authors (22) investigated this issue in a cohort of healthy individuals younger than 40 years of age, showing that EI values ≤ 0.35% should be considered normal for volumetric measurements performed with 10-mm collimation, 50 mAs, and a standard reconstruction algorithm; those authors found that the EI was not significantly influenced by age in that age group, a finding that is consistent with those of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…We did not include a group of never-smokers since previous studies have shown that non-smokers generally do not develop emphysema [8,10,15]. In the studies by Tylen et al and Vikgren et al [10,15], which included considerably older subjects, 60Á67 years old, emphysema was diagnosed in only one of 32 (3%) never-smokers and none of 26 never-smokers, respectively. It could be criticized that only one experienced thoracic radiologist evaluated the HRCT.…”
Section: Limitations and Strengthmentioning
confidence: 99%
“…11). Progressive bronchial alterations with increasing age were also demonstrated by Vikgren et al [39]. This phenomenon may be due to physiological changes in the ageing lung, causing a reduction in arterial oxygen pressure, leading to both hypoxic bronchodilatation and hypoxic vasoconstriction.…”
Section: Bronchial Dilatationmentioning
confidence: 86%
“…9a,b). Vikgren et al showed that sub-pleural nodularity was present in a significant proportion of normal subjects in their study, a finding they attributed to age-related change [39]. The cause of these minute subpleural nodules was not established, but the authors speculate that they may be the result of some earlier disease or exposure [39].…”
Section: Nodularitymentioning
confidence: 92%